1993
DOI: 10.1080/02643299308253455
|View full text |Cite
|
Sign up to set email alerts
|

Auditory atonalia for melodies

Abstract: We present the detailed analysis of a patient, GL, who presents auditory atonalia as a consequence of brain damage. GL was found to be unable to use tonal knowledge in the interpretation of melodic closure, in discrimination as well as in preference of melodies. This breakdown in the tonal representation of melodic patterns occurred in the presence of accurate encoding of melodic contour and, to some extent, of interval sizes. It also occurred in isolation from disturbances in the processing of temporal inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 46 publications
(43 reference statements)
1
48
0
1
Order By: Relevance
“…Employing both implicit and explicit tasks, however, Omigie, Pearce, and Stewart (2012) reported that amusic individuals were impaired at differentiating between high and low probability melodic events, despite intact implicit processing. The dissociation between implicit and explicit performance of musical structure has also been reported for individuals with acquired 6 amusia (Peretz, 1993;Tillmann, Peretz, Bigand, & Gosselin, 2007). These findings suggest that these two forms of knowledge are accessed using independent strategies.…”
Section: Experiments 1: Music-syntactic Processingmentioning
confidence: 55%
“…Employing both implicit and explicit tasks, however, Omigie, Pearce, and Stewart (2012) reported that amusic individuals were impaired at differentiating between high and low probability melodic events, despite intact implicit processing. The dissociation between implicit and explicit performance of musical structure has also been reported for individuals with acquired 6 amusia (Peretz, 1993;Tillmann, Peretz, Bigand, & Gosselin, 2007). These findings suggest that these two forms of knowledge are accessed using independent strategies.…”
Section: Experiments 1: Music-syntactic Processingmentioning
confidence: 55%
“…Isolated deficits of 'amelodia' and arrhythmia have been reported in the amusia literature for perceptual, productive, and musical reading tasks [4,13,30,37,38,[40][41][42]62]. Separate cognitive representations of melody and rhythm have also been proposed in the developmental [62,63] and normal adult literature [43,60,62], supporting the general applicability of this distinction.…”
Section: Introductionmentioning
confidence: 83%
“…Although the details of syntactic structure in the two domains are quite different (Keiler, 1978), it is this very fact that makes their comparison useful for sifting between domain-general and domain-speci c or "modular" cognitive processes. To illustrate this idea, we report a study that uses music to examine the language-speci city of a known neural correlate of syntactic processing, the P600 or "syntactic positive shift" brain potential (Hagoort, Brown, & Groothusen, 1993;Osterhout & Holcomb, 1992, 1993). …”
Section: Introductionmentioning
confidence: 99%